PM10 SAMPLING ON FORT RILEY, KANSAS -- SPRING 2012 - Bradley, Jason Bradley (My University, 2013)
Burning grass and other vegetation is a historic concept. Throughout the Flint Hills of Kansas, it is an annual event each spring in March and April. Burning is gaining more attention due to health and safety concerns. First responders, personnel managers, and health officials prepare for the 60 days of smoke generated from these events. On average, Kansas burns between one and two million acres each year (Kansas Department of Health and Environment, Smoke Manage Plan, 2010). Burning helps the landowners prepare the pasture for summer grazing. It helps with grass growth, germination of forbs, and control of woody vegetation. The process of burning produces particulate matter (PM) and releases volatile organic compounds (VOCs). These additions affect the air quality. Increased particulate matter and increased ozone levels (secondary to the increases in VOCs) have mechanical and physiological effects within people. It affects healthy individuals and those with disease. Decreased visibility affects traffic safety and the smoke plumes are large enough to be seen on satellite images. These health and safety concerns have opened the door for larger organizations, such as Fort Riley, to monitor sources and develop regulations to mitigate the health and safety concerns. This study occurred in the spring of 2012 as Fort Riley’s first look into this issue. It utilized the SKC Deployable Particulate Sampler (DPS) issued by the U.S. Army Public Health Command. These units, seven in total and six deployed, sampled 24 hours a day seven days a week from March 15th to April 12th, 2012. The samplers are continuous flow monitors that collect 24 hour accumulated particulates of 10 micrometers and smaller. Utilizing the DPS flow rates over time and weighing the filters that captured the particulate matter (10 µm and smaller), the micrograms of particulate per meter cubed of air (µg/m³) are calculated for that day (i.e., PM10). The data collected from the samplers has been statistically evaluated for the PM10 mean by location and across all locations, and for statistical significance between locations. This paper addresses the variability among the sampling sites, establishes the need for a different type of sampling equipment to accomplish real-time sampling, and sets a foundation for further studies to occur on Fort Riley. Additionally, Fort Riley is using this data to compare the relationship between elevated PM levels and medically-coded upper respiratory encounters at Irwin Army Hospital.
Keywords: PM10; Public health; Ft.Riley, Kansas; Public Health (0573)